Upaya Meningkatkan Hasil Belajar PKn Melalui Metode Bermain Peran Dengan Model Pembelajaran Cooperative Learning Kelas V Sekolah Dasar - Sulaiman Sulaiman (JURNAL PENDIDIKAN ROKANIA, 2018)
This action research is generally aimed to improve the learning outcomes of PPKN on shared decision-making materials through role-playing methods in grade V SD students through the implementation of cooperative learning method in the first semester of SDN 003 Rambah Hilir. The data in this study were collected using tests, student observation sheets, teacher observation sheets, and field notes. The type of research is classroom action research. The research procedure consists of planning, execution, observation and reflection. The results revealed that preliminary results showed that students' absorptive capacity in the pre cycle earned a formative average score of 68 from the established KKM 75. From the 23 students only 12 students or 52% who scored 75 and above, while the other 10 students 43% scored below 75. For the first cycle students achieved 69% completeness and in the second cycle of 96%. Based on the research conducted, it can be concluded that there is a significant increase if the teacher uses the method and the right way of learning so that students can learn with passion and achieve the achievement that we expect